MACEDONIAN HOUSE FROM THE BEGINNING OF THE XIX CENTURY IN VELES - Nikoljski panevski, Elena; Dragana Trajkovska (Ss. Cyril and Methodius University in Skopje, 2018)
A thematic examination has been made of constructive and aesthetic values in traditional Macedonian architecture in the city of Veles, in order to endorse the architectural categories developed in all national constructive creations on Macedonian ground. Although the examination was focused on one city of Macedonia, we separated the main features of national architecture which are distinctive for this surrounding. The values that differentiate this region from the others were analyzed in detail.. This paper comprises a few methods of examination. These methods helped us to formulate all the parameters used by the national builders. The presented examination leads to the conclusion that national architecture abounds with aesthetic values. The national builder, with his extraordinary building skills, succeeded in presenting them in their true light. Our obligation today is to validate and preserve it in its originality.
Keywords: examination; examination methods; traditional; Macedonian architecture in Veles; interior organization; rooms; positioning the rooms; constructive skill; national constructor; meaning and value of traditional houses